MAREA VERDE - Piotrkowski, Guido; Bianchi, Paula Daniela (Paralelo 31, 2021)
Resumem: El ensayo visual y verbal, con fotografías del artista argentinoGuido Piotrkowski y texto de la investigadora Paula D. Bianchi, documentapoéticamente las manifestaciones callejeras del movimiento Marea Verde.Palabras clave: Marea Verde; Fotografía; La calle; Aborto. MAREA VERDE Resumo: O ensaio visual e verbal, com fotografias do artista argentino GuidoPiotrkowski e texto da pesquisadora Paula D. Bianchi documentam, poeticamente, as manifestações de rua do movimento Marea Verde.Palavras-chave: Marea Verde; Fotografia; A rua; Aborto.GREEN TIDEAbstract:The visual and verbal essay, with photographs by Argentine artist Guido Piotrkowski and text by researcher Paula D. Bianchi, poetically document the street demonstrations of the Marea Verde movement.Keywords: Green Tide; Photography;  The street; Abortion.